SITE FORMATION AND CORROSION PROCESSES: A Comparative Analysis of Condor and Stormy Petrel Wreck Sites - Alexander, Hoyt L. (East Carolina University, 2019)
Submerged cultural resources abound in North Carolina waters, and two Civil War blockade runners built, launched, and sunk within months of each other provide an opportunity to review site formation processes through a multi-disciplinary lens. The incorporation of historical, electrochemical, meteorological, geographic information science, and structured query language methods provides a more comprehensive understanding of the processes affecting Condor and Stormy Petrel. This knowledge can be used to inform management decisions regarding the preservation of valuable cultural resources and the longevity of those resources.
Keywords: In Situ; Site Formation; GIS; SQL; Storm Analysis; Condor; Stormy Petrel; Ecorr; Corrosion Potential; Pourbaix Diagram; PostGIS; PostgreSQL; Maritime; Archaeology; Shipwrecks--North Carolina--19th century--History; Ships--Corrosion; Blockade--North Carolina--History; United States--History--Civil War, 1861-1865--Naval operations